2016
DOI: 10.3389/fendo.2016.00033
|View full text |Cite
|
Sign up to set email alerts
|

Feeding a Modified Fish Diet to Bottlenose Dolphins Leads to an Increase in Serum Adiponectin and Sphingolipids

Abstract: Feeding a modified fish diet has been suggested to improve insulin sensitivity in bottlenose dolphins; however, insulin sensitivity was not directly measured. Since demonstrating an improvement in insulin sensitivity is technically difficult in dolphins, we postulated that directional changes in the hormone axis: fibroblast growth factor 21 (FGF21)/Adiponectin/Ceramide (Cer), could provide further support to this hypothesis. We measured 2-h post-prandial serum FGF21, total adiponectin, percent unmodified adipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 51 publications
(77 reference statements)
2
15
0
Order By: Relevance
“…Blocking ceramide production with SPT inhibitor myriocin in DIO mice led to increased levels of circulating high molecular weight adiponectin ( 59 ). This inverse relationship between adiponectin and ceramides has also been shown in rats ( 155 , 156 ) and dolphins.…”
Section: Preclinical Studies Of Adiponectin and Ceramidessupporting
confidence: 69%
“…Blocking ceramide production with SPT inhibitor myriocin in DIO mice led to increased levels of circulating high molecular weight adiponectin ( 59 ). This inverse relationship between adiponectin and ceramides has also been shown in rats ( 155 , 156 ) and dolphins.…”
Section: Preclinical Studies Of Adiponectin and Ceramidessupporting
confidence: 69%
“…Another example was a study investigating a dolphin condition similar to human metabolic syndrome using serum lipid profiles between two groups of dolphins, where high or low insulin were analyzed. The study found differences in phospholipid fatty acids in the two groups, which may play a role in the susceptibility to or development of an insulin-resistant-like state: the proteomic analysis of dolphin serum showed correlation of changes in the fatty acids with an insulin-sensitizing phenotype (Sobolesky et al, 2016).…”
Section: Cetacea (Order: Cetartiodactyla)mentioning
confidence: 90%
“…In a parallel study supported by proteomic analysis, differences in serum lipid profiles between two groups of dolphins, with high or low insulin, found differences in phospholipid fatty acids. Shifting the dolphin diet to fish rich in odd chain saturated fatty acids, such as C17:0, resulted in increased serum levels of the insulin-sensitizing hormone adiponectin and serum sphingosines consistent with an insulinsensitizing phenotype (Sobolesky et al, 2016). A better understanding of the networks activated by the mechanisms regulating adiponectin in dolphins could aid research of metabolic syndrome and diabetes affecting human populations.…”
Section: Applications Of Marine Mammal Unique Adaptations: Marine Biomentioning
confidence: 99%
“…Parallel reaction monitoring was previously utilized to measure one of the 11 proteins, adiponectin, from Table 1 . Dolphin (human-care and free-ranging) serum concentrations of adiponectin measured by reaction monitoring 22 26 41 range between 2.3–47.9 μg/ml. Adiponectin concentrations, measured by reaction monitoring in humans, range between 0.02 μg/ml and 3 μg/ml 42 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Many insightful studies of marine mammal physiology and health have focused on oxygen transport, antioxidant, metabolic, and clinical laboratory-relevant proteins in the blood; however, comparative studies describing the circulating serum proteome in marine mammals have not been extensively interrogated for novel serum phenotypes that could underlie significant alternative mechanisms of protection and/or metabolic regulation. To extend the discovery of phenotypic determinants in the serum that may promote the ability of marine mammals to counter stress, we created a normalized spectral abundance factor rank-list of high abundance serum proteins from bottlenose dolphins ( Tursiops truncatus ) 22 alongside undepleted human and pig serum proteomes generated in-house. Outlier ranked proteins were listed and one of the outlier proteins, Vanin-1, was chosen to validate the rank differences.…”
mentioning
confidence: 99%